INFLUENCE OF STORE ATTRIBUTES TOWARDS CONSUMER PERCEPTION AT INDOMARET IN MANADO CITY - Pangemanan, Reynaldo; Tielung, Maria (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Minimarket has become popular in Manado today's society, such as selling goods directly to consumers for private use which the buyer intends to consume the product sold. This study took place in Manado city, North Sulawesi. The objectives of this research are to analyze the influence of store attributes towards consumer perception to indomaret minimarket in Manado both simultaneously and partially .This research is the causal type of research where it will investigate the influence of elements on consumer perception using Multiple Regression models to answer the research problem. Conclusions of this study are There is a significant influence of store image, product assortment, product availability, discounts, and distance simultaneously. This study reveals that store attributes is a mental decision that made by the consumer has a strong influence factor in order to buy a product, when consumer go for purchasing, they prefer to purchase a product according to customer needs. Indomaret marketing division should be more focused on discount application because according to research prices the most in demand by consumers, so as to increase sales Indomaret in Manado. Keywords: consumer perception, store image, product, discounts.